Analysis of the neurology consultations in the emergency department and diagnostic accuracy of emergency physicians for the neurologic emergencies (Annals of Medical Research, 2021)
Aim: The aims of this study are twofold: Firstly, it aims at determining the profile of patients who are requested to consult neurology in the emergency department. Secondly, it aims at evaluating the concordance between the pre-consultation neurologic diagnoses and the post-consultation diagnoses in the emergency department.Material and Methods: The study presents a retrospective evaluation of the records of the patients who were admitted to the emergency department and requested neurology consultation between July 1st, 2018 and July 1st, 2019. Demographic characteristics, admission types, diagnostic imaging procedures, requested consultations, pre-consultation diagnoses, duration of neurology consultation, post-consultation diagnoses, and outcome of patients in the emergency department are included in the analysis.Results: Neurology consultation was requested for 347 (0.83%) patients among 41,850 emergency department admissions during the study period. The female/male distribution of consulted patients was 50.7% vs. 49.3%. The ambulatory admission and ambulance arrival rates to the emergency department were 51.9% (n = 180) and 48.1% (n = 167), respectively. Only neurology consultation was requested for 227 patients (65.4%), while the additional consultation/consultations other than neurology consultation were needed for 120 (34.6%) patients. Diagnostic accuracy was 60.8% for the study sample and 71.2% for the patients requiring neurology consultation only. The diagnostic accuracy of ischemic stroke was 84.7%. The hospitalization rate of the study sample was 64% (n = 222). The majority of hospitalized patients were admitted by the neurology department (n = 182). Conclusion: The high accuracy of the diagnosis of ischemic stroke in this study may result from all neurology consultations in our emergency department being requested by the emergency physician specialists. On the other hand, carefully integrated algorithms and neurological examination training will be useful to improve diagnostic accuracy in other neurological emergencies.